TNF-α, IL-4Rα AND IL-4 Polymorphisms in Mild to Severe Asthma from Italian Caucasians. (January 2013) - Ricciardolo, F.L.M.; Sorbello, V.; Silvestri, M.; Giacomelli, M.; Debenedetti, V.M.G.; Malerba, M.; Ciprandi, G.; Rossi, G.A.; Rossi, A.; Bontempelli, M.
Asthma is a chronic airway inflammatory disease associated with airway hyperresponsiveness which affects subjects with genetic predisposition. An association has been reported between some polymorphisms in various cytokine genes and asthma. Most of them are single nucleotide polymorphisms (SNPs). These polymorphisms are detected in the protein coding sequence or in the promoter region thus influencing cytokine production. We investigated the involvement of SNP mapping in 5 cytokine genes in mild to severe asthmatics of Italian Caucasians. The frequency of alleles and genotypes, relatively to 10 allelic specificities of the cytokine genes, was defined in 57 asthmatics and in 124 control subjects by a Polymerase Chain Reaction-Sequence Specific Primer method. TNF-α -308A and TNF-α -238A allele frequencies were higher in asthmatics than in controls (p<0.001). Significant differences in the frequency of IL-4 -590T allele and of IL-4Rα + 1902A allele were also detected in asthmatics in comparison with controls (p<0.001 and p=0.005, respectively). Similarly, IL-1α -889C allele was present in 84.1% of asthmatics and in 70.2% of controls (p=0.013). Furthermore, the IL-4Rα + 1902A/A and IL-1α -889C/C homozygous conditions and the TNF-α -308G/A, TNF-α -238G/A, IL-4 -590T/C and IL-10 -1082G/A heterozygous conditions were significantly associated with asthma (p<0.05). ACA haplotype of IL-10 was observed only in asthmatic patients. This study reports, for the first time, the frequency of 10 different single nucleotide polymorphisms in 5 cytokine genes in the Italian Caucasians. Furthermore, we also indicate that in our population some single nucleotide polymorphisms are associated with mild to severe bronchial asthma.